(untitled) (Tri-Chandra Journal of Anthropology, 2025)
The purpose of this ethnographic study is to investigate the factors that have influenced the transmission of indigenous knowledge from generation to generation among Pariyar musicians of Rupa Rural Municipality, Mulpani & Saaldada, Kaski District, Gandaki Province of Nepal, especially in the context of Panche baja. It examines the current situation of challenges in passing on this knowledge and skills to the next generation. Additionally, taking into account the three main Panche baja instruments—Sahana, Narsingha, and Dholaki—this study recounts the indigenous knowledge system that was passed down from the ancestors and is now in use. In order to examine the phenomena from an insider’s perspective, this anthropological study offers case studies. These findings, particularly when considering the system of knowledge transmission from the past to the future, could serve as the basis for education, conservation efforts, and innovation as well as attributes to enhance local knowledge and its transfer system, not just in Rupa but also in other societies of Nepal.